PENGARUH SUASANA TOKO DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA TOKO YUDI JAYA ELEKTRONIK DI SAMARINDA - Pratiningsih, Irma - (EKONOMIA, 2019)
The influence of the store atmosphere anda location on consumer buying interest in the electronic yudi jaya shop in samarinda. Marketing Management Departement Faculty of Economics, University 17 Agust 1945 Samarinda. Guided by Mrs. Mardiana and Mr. Sarwo Eddy Wibowo.The purpose of this study was to determine the effect of store atmosphere and location on consumer buying interest at Yudi Jaya Electronik shop in Samarinda. This research was conducted at Yudi Jaya ElectronikSamarinda store, the samples taken were 96 respondents with incidental sampling method. Data collection by distributing questionnaires using a 5-point likert scale to measure each indicator. The analysis technique used is multiple linear regression. The results of this study indicate that the store atmosphere and location has a significant effect simultaneously on consumer buying interst in the Yudi Jaya Electronik shop in Samarinda. The atmosphere of the store and location have a significant effect simultaneously on consumer buying interest in the Yudi Jaya Electronik shop in Samarinda